Global Trends in SPSS Training for Students: a Step Towards Improved Research Competence - Nanere, Marthin; Tabelessy, Walter; Leuhery, Ferdy; Tubalawony, Jacsy; Saununu, Siska (Asian Journal of Community Services, 2025)
The statistics training using the SPSS application in the Management Department, Faculty of Economics and Business, Universitas Pattimura aims to enhance students' understanding and skills in analyzing quantitative research data. In today’s era of technological advancement, proficiency in statistics and its applications is crucial for students to produce competent and high-quality research. This training involved 22 students and was conducted in the Marketing and Business Laboratory through lectures, discussions, and hands-on practice. The speaker, a lecturer from La Trobe University, Australia, provided insights into using SPSS for both descriptive and inferential data analysis. The step-by-step application of SPSS for descriptive and inferential statistics was demonstrated with practical examples, making it easier for students to understand.